Lanthanum-titanium alloy target material as well as preparation method and application thereof
By adding lanthanum and molybdenum elements to the titanium target, the problem of low density of existing titanium targets is solved, and the high density and good mechanical properties of lanthanum titanium alloy targets are achieved, which is suitable for a variety of application fields.
Patent Information
- Application Number
- CN202411994444.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
The density of existing titanium targets is low, affecting their performance in a variety of application fields.
The lanthanum titanium alloy target is used to promote the uniformity and density of the target structure by adding lanthanum and molybdenum. The addition of lanthanum elements helps to reduce porosity, while molybdenum elements improve the mechanical properties of the target materials.
It significantly improves the density of lanthanum titanium alloy targets, enhances its mechanical properties, and is suitable for a variety of application fields.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of target materials, and in particular to a lanthanum-titanium alloy target material and a preparation method and application thereof. Background Art
[0002] As a material with special uses, the target material has a strong application purpose and a clear application background. Sputtering targets have been widely used in many fields such as decoration, molds, glass, electronic devices, semiconductors, magnetic recording, flat panel displays and solar cells.
[0003] Titanium target is a typical metal target. It is widely used in PVD because of its good corrosion resistance and electromagnetic shielding performance, and titanium can be used as a decorative and protective coating on other metal surfaces.
[0004] The density of the titanium target material produced in the related art is low. Summary of the invention
[0005] The present application has been made in view of the above-mentioned problems, and an object of the present application is to provide a lanthanum-titanium alloy target having a high density.
[0006] Specifically, the first aspect of the present application provides a lanthanum-titanium alloy target, including the following preparation raw materials:
[0007] Titanium source, lanthanum source and molybdenum source.
[0008] According to one of the technical solutions of the target material in this application, at least the following beneficial effects are achieved:
[0009] The raw materials for preparing the alloy target in the present application include titanium source, lanthanum source and molybdenum source; among them, lanthanum element can play a role in grain refinement, promote the uniformity of the target material structure, and thus improve the density of the target material; the addition of lanthanum element can reduce the porosity in the target material, thereby improving the density. Lanthanum has a strong ability to bind with oxygen, which helps to reduce the generation of oxide impurities, thereby reducing pores and improving density; the alloy target formed by molybdenum element has a higher melting point, higher strength and good thermal conductivity, which can enhance the mechanical properties of the target material.
[0010] According to some embodiments of the present application, the lanthanum-titanium alloy target material includes the following preparation raw materials in parts by weight:
[0011] 100 parts of titanium source, 0.2 to 0.8 parts of lanthanum source and 5 to 10 parts of molybdenum source.
[0012] According to some embodiments of the present application, the titanium source is modified sponge titanium.
[0013] According to some embodiments of the present application, the method for preparing the modified titanium sponge comprises the following steps:
[0014] After oxidizing the titanium sponge, an oxidized titanium sponge is obtained;
[0015] The titanium oxide sponge and the amino silane coupling agent are mixed and then refluxed for reaction.
[0016] According to some embodiments of the present application, the amino silane coupling agent includes bis-[3-(triethoxysilyl)-propyl]-amine.
[0017] According to some embodiments of the present application, the mass ratio of the titanium oxide sponge to the amino silane coupling agent is 100:1-2.
[0018] According to some embodiments of the present application, the mesh size of the titanium sponge is 2000 mesh to 8000 mesh.
[0019] According to some embodiments of the present application, the mesh size of the titanium sponge is 5000 to 8000 mesh.
[0020] According to some embodiments of the present application, the oxidant selected for the oxidation is a mixture of sulfuric acid and hydrogen peroxide.
[0021] According to some embodiments of the present application, the oxidant consists of concentrated sulfuric acid and hydrogen peroxide solution.
[0022] According to some embodiments of the present application, the volume ratio of the concentrated sulfuric acid to the hydrogen peroxide solution is 2-4:1.
[0023] According to some embodiments of the present application, the mass fraction of the concentrated sulfuric acid is 95% to 98%.
[0024] According to some embodiments of the present application, the concentration of the hydrogen peroxide solution is 28% to 30%.
[0025] According to some embodiments of the present application, the oxidation temperature is 50°C to 60°C.
[0026] According to some embodiments of the present application, the oxidation time is 10 min to 30 min.
[0027] According to some embodiments of the present application, the solvent for the reflux reaction is toluene.
[0028] According to some embodiments of the present application, the temperature of the reflux reaction is 60°C to 70°C.
[0029] According to some embodiments of the present application, the reflux reaction time is 10 h to 12 h.
[0030] According to some embodiments of the present application, the lanthanum source is a carboxylated lanthanum source.
[0031] According to some embodiments of the present application, the method for preparing the carboxylated lanthanum source comprises the following steps:
[0032] The silane, the template agent and the ammonia water are mixed and reacted, and after the reaction is completed, the solid and the liquid are separated, and the solid phase is collected to obtain a first mixture;
[0033] The first mixture is hydrolyzed, and then the lanthanum salt is added to react.
[0034] According to some embodiments of the present application, the silane includes isobutyltriethoxysilane or cyanotrimethylsilane.
[0035] According to some embodiments of the present application, the mass ratio of isobutyltriethoxysilane to cyanotrimethylsilane is 1:3-4.
[0036] According to some embodiments of the present application, the template agent includes alkylammonium bromide.
[0037] According to some embodiments of the present application, the alkylammonium bromide includes hexadecyltrimethylammonium bromide.
[0038] According to some embodiments of the present application, the lanthanum salt includes at least one of lanthanum chloride or lanthanum nitrate.
[0039] According to some embodiments of the present application, the mass ratio of the silane to the template is 1:0.2-0.4.
[0040] According to some embodiments of the present application, the mass ratio of the silane to the lanthanum salt is 1:10-20.
[0041] According to some embodiments of the present application, the mass fraction of the ammonia water is 20% to 25%.
[0042] According to some embodiments of the present application, water needs to be added after the mixing and before the reaction.
[0043] According to some embodiments of the present application, the volume mass ratio of water to ammonia water is 100 mL: 20 g to 30 g.
[0044] According to some embodiments of the present application, the reaction time after mixing is 10 hours to 20 hours.
[0045] According to some embodiments of the present application, the temperature of the reaction after mixing is 50°C to 70°C.
[0046] According to some embodiments of the present application, a sulfuric acid solution is added during the hydrolysis process.
[0047] According to some embodiments of the present application, the volume ratio of water to sulfuric acid solution is 1:0.5-1.5.
[0048] According to some embodiments of the present application, the mass fraction of the sulfuric acid solution is 40% to 50%.
[0049] According to some embodiments of the present application, the hydrolysis temperature is 80°C to 90°C.
[0050] According to some embodiments of the present application, the hydrolysis time is 15 h to 25 h.
[0051] According to some embodiments of the present application, the reaction time after the lanthanum salt is added is 10 hours to 15 hours.
[0052] According to some embodiments of the present application, the reaction temperature after the lanthanum source is added is 80°C to 90°C.
[0053] According to some embodiments of the present application, the molybdenum source is mercapto-modified molybdenum oxide.
[0054] According to some embodiments of the present application, the method for preparing the mercapto-modified molybdenum oxide comprises the following steps:
[0055] Thioglycolic acid, molybdenum oxide and water are mixed and processed.
[0056] According to some embodiments of the present application, the mass ratio of molybdenum oxide to thioglycolic acid is 1:0.02-0.2.
[0057] According to some embodiments of the present application, the mass volume ratio of the molybdenum oxide and water is 0.1g~1g:100mL.
[0058] According to some embodiments of the present application, the molybdenum oxide is molybdenum trioxide.
[0059] According to some embodiments of the present application, the treatment is ultrasonic treatment.
[0060] According to some embodiments of the present application, the ultrasonic treatment time is 1 h to 3 h.
[0061] According to some embodiments of the present application, the power of the ultrasonic treatment is 100W to 200W.
[0062] In the present application, modified sponge titanium is selected as the titanium source, carboxylated lanthanum source and mercapto-modified molybdenum oxide are selected as the molybdenum source; the sponge titanium is modified to introduce amino groups on the surface of the sponge titanium, and the sponge titanium serves as a matrix to play a supporting role; the carboxylated lanthanum source and mercapto-modified molybdenum oxide are filled into the voids of the sponge titanium, which is beneficial to the uniform distribution of lanthanum and molybdenum elements in the target material. At the same time, the lanthanum source is carboxylated and the molybdenum oxide is mercapto-modified to enhance the interaction force between the molybdenum source and the lanthanum source and the sponge titanium, which is beneficial for the molybdenum source and the lanthanum source to interact with the titanium source in situ, further improving the uniformity of the organization, thereby further improving the density of the target material.
[0063] The second aspect of the present application provides a method for preparing the above-mentioned lanthanum-titanium alloy target, comprising the following steps:
[0064] The raw materials are mixed, hydrogenated, crushed, cold pressed and hot isostatically pressed.
[0065] In the present application, the titanium source in the raw material is refined by hydrogenating the raw material, thereby further ensuring the uniformity of the mixing of titanium, lanthanum and molybdenum elements, and providing a guarantee for the density and purity of the target material; the present application preliminarily shapes the raw material by cold pressing and then hot isostatic pressing and sintering, thereby obtaining a more uniform element distribution and organizational morphology, thereby improving the density of the target material.
[0066] According to some embodiments of the present application, the hydrogenation temperature is 500°C to 600°C.
[0067] According to some embodiments of the present application, the hydrogen pressure of the hydrogenation is 0.1 MPa to 2 MPa.
[0068] According to some embodiments of the present application, the hydrogenation time is 2 h to 3 h.
[0069] According to some embodiments of the present application, the mesh size after crushing is 10000 to 20000 mesh.
[0070] According to some embodiments of the present application, the pressure of the cold press forming is 150 MPa to 250 MPa.
[0071] According to some embodiments of the present application, the cold pressing time is 5 minutes to 15 minutes.
[0072] According to some embodiments of the present application, the hot isostatic pressing sintering pressure is 100 MPa to 200 MPa.
[0073] According to some embodiments of the present application, the temperature of the hot isostatic pressing sintering is 1000°C to 1400°C.
[0074] According to some embodiments of the present application, the hot isostatic pressing sintering time is 3 hours to 20 hours.
[0075] According to some embodiments of the present application, the hot isostatic pressing sintering includes a first stage sintering, a second stage sintering and a third stage sintering.
[0076] According to some embodiments of the present application, the pressure of the first sintering stage is 100 MPa to 120 MPa.
[0077] According to some embodiments of the present application, the temperature of the first sintering stage is 1000°C to 1100°C.
[0078] According to some embodiments of the present application, the time of the first sintering stage is 0.5h to 3h.
[0079] According to some embodiments of the present application, the hot isostatic pressing sintering includes a first stage sintering, a second stage sintering and a third stage sintering.
[0080] According to some embodiments of the present application, the pressure of the second sintering stage is 140 MPa to 160 MPa.
[0081] According to some embodiments of the present application, the temperature of the second sintering stage is 1280°C to 1320°C.
[0082] According to some embodiments of the present application, the second sintering time is 0.5h to 3h.
[0083] According to some embodiments of the present application, the pressure of the third sintering stage is 180 MPa to 200 MPa.
[0084] According to some embodiments of the present application, the temperature of the third sintering stage is 1350°C to 1400°C.
[0085] According to some embodiments of the present application, the third sintering time is 0.5h to 3h.
[0086] The third aspect of the present application provides the use of the above-mentioned lanthanum-titanium alloy target in the preparation of sputtering films. DETAILED DESCRIPTION
[0087] In order to make the purpose, technical solutions and advantages of the present application clearer, the present application is described and illustrated below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not intended to limit the present application. Based on the embodiments provided in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application.
[0088] Obviously, the following descriptions are only some examples or embodiments of the present application. For ordinary technicians in this field, the present application can also be applied to other similar scenarios without creative work. In addition, it can also be understood that although the efforts made in this development process may be complicated and lengthy, for ordinary technicians in the field related to the content disclosed in this application, some changes in design, manufacturing or production based on the technical content disclosed in this application are just conventional technical means, and should not be understood as insufficient content disclosed in this application.
[0089] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0090] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0091] Sponge titanium powder was purchased from Qinghe County Xingxin New Material Technology Co., Ltd. with a mesh size of 5000 mesh.
[0092] Example 1
[0093] This embodiment is a lanthanum-titanium alloy target material, which is composed of the following raw materials in parts by weight:
[0094] 100 parts of titanium source, 0.5 parts of lanthanum source and 8 parts of molybdenum source.
[0095] The titanium source is modified sponge titanium, the lanthanum source is carboxylated lanthanum source, and the molybdenum source is mercapto-modified molybdenum oxide.
[0096] The preparation method of modified titanium sponge consists of the following steps:
[0097] Sponge titanium and an oxidant (a mixture of concentrated sulfuric acid (mass fraction 98%) and hydrogen peroxide solution (mass fraction 28%), the volume ratio of concentrated sulfuric acid to hydrogen peroxide solution is 3:1, and the mass volume ratio of sponge titanium to the oxidant is 1 g:10 mL) are mixed and oxidized (temperature 60°C, time 20 min) to obtain oxidized sponge titanium;
[0098] The titanium oxide sponge, aminosilane coupling agent (bis-[3-(triethoxysilyl)-propyl]-amine) and toluene were mixed and refluxed for reaction (temperature of 60°C for 10 hours); after the reaction was completed, the solid and liquid were separated, and the solid phase was collected, washed and dried.
[0099] The mass ratio of the titanium oxide sponge to the amino silane coupling agent is 100:1.4.
[0100] The preparation method of the carboxylated lanthanum source consists of the following steps:
[0101] Silane, a template (hexadecyltrimethylammonium bromide), ammonia water (mass fraction of 25%) and water (mass volume ratio of ammonia water to water is 20 g:100 mL) are mixed and reacted (reaction temperature is 60° C., reaction time is 15 h), solid-liquid separation is performed after the reaction is completed, and the solid phase is collected to obtain a first mixture;
[0102] The first mixture and sulfuric acid solution (the mass fraction of sulfuric acid is 45%, and the volume ratio of sulfuric acid solution to water in the reaction process after mixing is 1:1) are mixed and hydrolyzed (the hydrolysis temperature is 80°C and the time is 20h), and then lanthanum salt (lanthanum chloride) is added to react (the reaction temperature is 80°C and the time is 10h). After the reaction is completed, the solid and liquid are separated, and the solid phase is collected, washed and dried.
[0103] The silane is composed of isobutyltriethoxysilane and cyanotrimethylsilane, the mass ratio of isobutyltriethoxysilane to cyanotrimethylsilane is 1:3.5; the mass ratio of silane to template is 1:0.2; the mass ratio of silane to lanthanum salt is 1:18.
[0104] The preparation method of mercapto-modified molybdenum oxide consists of the following steps:
[0105] Thioglycolic acid, molybdenum oxide (molybdenum trioxide, mesh size of 20000 mesh) and water (mass volume ratio of molybdenum oxide to water is 1g:100mL) are mixed and then ultrasonically treated (ultrasonic power of ultrasonic treatment is 200W, time is 3h). After the treatment is completed, solid-liquid separation is performed, and the solid phase is collected, washed and dried.
[0106] The mass ratio of molybdenum oxide to thioglycolic acid is 1:0.1.
[0107] The preparation method of the lanthanum-titanium alloy target in this embodiment consists of the following steps:
[0108] S1, mixing the titanium source, molybdenum source and lanthanum source by ball milling (ball milling mixing time is 10 hours) to obtain a mixed powder;
[0109] S2, hydrogenating the mixed powder in a hydrogenation furnace, evacuating to 0.01Pa before hydrogenation, introducing hydrogen after evacuation, controlling the hydrogen pressure to be 1MPa, the hydrogenation temperature to be 500°C, the heating rate to be 10°C / min, and keeping at 500°C for 2h after the heating is completed. After the hydrogenation is completed, cooling to 25°C, crushing to 20000 mesh (under protective atmosphere), and obtaining hydrogenated powder;
[0110] S3, cold pressing the hydrogenated powder at 200 MPa for 10 min to obtain a cold pressed mixture;
[0111] S4, hot isostatic pressing the cold pressed mixture, and cooling it with the furnace after sintering;
[0112] The sintering procedure of hot isostatic pressing is as follows:
[0113] The first stage of sintering: pressure 100MPa, temperature 1000℃ (heating rate 10℃ / min), time 2h;
[0114] The second stage of sintering: pressure 150MPa, temperature 1300℃ (heating rate 10℃ / min), time 1h;
[0115] The third sintering stage: pressure is 200 MPa, temperature is 1400°C (heating rate is 10°C / min), and time is 0.5h.
[0116] Example 2
[0117] This embodiment is a lanthanum-titanium alloy target material, which is different from the embodiment 1 in that:
[0118] 100 parts of titanium source, 0.2 parts of lanthanum source and 10 parts of molybdenum source.
[0119] Raw materials for the preparation of modified titanium sponge:
[0120] The mass ratio of the titanium oxide sponge to the amino silane coupling agent is 100:1.
[0121] In the raw materials for preparing the carboxylated lanthanum source:
[0122] The silane is composed of isobutyltriethoxysilane and cyanotrimethylsilane, the mass ratio of isobutyltriethoxysilane to cyanotrimethylsilane is 1:3; the mass ratio of silane to template is 1:0.2; the mass ratio of silane to lanthanum salt is 1:10.
[0123] The raw materials for preparing mercapto-modified molybdenum oxide include:
[0124] The mass ratio of molybdenum oxide to thioglycolic acid is 1:0.2.
[0125] Example 3
[0126] This embodiment is a lanthanum-titanium alloy target material, which is different from the embodiment 1 in that:
[0127] 100 parts of titanium source, 0.8 parts of lanthanum source and 5 parts of molybdenum source.
[0128] Raw materials for the preparation of modified titanium sponge:
[0129] The mass ratio of the titanium oxide sponge to the amino silane coupling agent is 100:2.
[0130] In the raw materials for preparing the carboxylated lanthanum source:
[0131] The silane is composed of isobutyltriethoxysilane and cyanotrimethylsilane, the mass ratio of isobutyltriethoxysilane to cyanotrimethylsilane is 1:4; the mass ratio of silane to template is 1:0.2; the mass ratio of silane to lanthanum salt is 1:20.
[0132] The raw materials for preparing mercapto-modified molybdenum oxide include:
[0133] The mass ratio of molybdenum oxide to thioglycolic acid is 1:0.02.
[0134] Example 4
[0135] This embodiment is a lanthanum-titanium alloy target material, which is different from the embodiment 1 in that:
[0136] 100 parts of titanium source, 0.3 parts of lanthanum source and 7 parts of molybdenum source.
[0137] Raw materials for the preparation of modified titanium sponge:
[0138] The mass ratio of the titanium oxide sponge to the amino silane coupling agent is 100:1.2.
[0139] In the raw materials for preparing the carboxylated lanthanum source:
[0140] The silane is composed of isobutyltriethoxysilane and cyanotrimethylsilane, and the mass ratio of isobutyltriethoxysilane to cyanotrimethylsilane is 1:3.4; the mass ratio of silane to template is 1:0.2; and the mass ratio of silane to lanthanum salt is 1:12.
[0141] The raw materials for preparing mercapto-modified molybdenum oxide include:
[0142] The mass ratio of molybdenum oxide to thioglycolic acid is 1:0.12.
[0143] Example 5
[0144] This embodiment is a lanthanum-titanium alloy target material, which is different from the embodiment 1 in that:
[0145] 100 parts of titanium source, 0.2 parts of lanthanum source and 5 parts of molybdenum source.
[0146] Raw materials for the preparation of modified titanium sponge:
[0147] The mass ratio of the titanium oxide sponge to the amino silane coupling agent is 100:1.
[0148] In the raw materials for preparing the carboxylated lanthanum source:
[0149] The silane is composed of isobutyltriethoxysilane and cyanotrimethylsilane, the mass ratio of isobutyltriethoxysilane to cyanotrimethylsilane is 1:3; the mass ratio of silane to template is 1:0.2; the mass ratio of silane to lanthanum salt is 1:10.
[0150] The raw materials for preparing mercapto-modified molybdenum oxide include:
[0151] The mass ratio of molybdenum oxide to thioglycolic acid is 1:0.02.
[0152] Example 6
[0153] This embodiment is a lanthanum-titanium alloy target material, which is different from Embodiment 5 in that:
[0154] The sintering procedure of the hot isostatic pressing sintering of the lanthanum-titanium alloy target in this embodiment is as follows:
[0155] The first stage of sintering: pressure 100MPa, temperature 1000℃ (heating rate 10℃ / min), time 2h;
[0156] The second stage of sintering: pressure is 150 MPa, temperature is 1300°C (heating rate is 10°C / min), and time is 1.5 h.
[0157] Example 7
[0158] This embodiment is a lanthanum-titanium alloy target material, which is different from Embodiment 5 in that:
[0159] The sintering procedure of the hot isostatic pressing sintering of the lanthanum-titanium alloy target in this embodiment is as follows:
[0160] The pressure is 150 MPa, the temperature is 1400°C (heating rate is 10°C / min), and the time is 3.5 h.
[0161] Example 8
[0162] This embodiment is a lanthanum-titanium alloy target material, which is different from Embodiment 7 in that:
[0163] The molybdenum source is molybdenum oxide (mesh size is 20000 mesh)
[0164] Example 9
[0165] This embodiment is a lanthanum-titanium alloy target material, which is different from Embodiment 7 in that:
[0166] The lanthanum source is lanthanum trioxide (mesh size is 20000 mesh)
[0167] Example 10
[0168] This embodiment is a lanthanum-titanium alloy target material, which is different from Embodiment 7 in that:
[0169] Titanium sponge is selected as the titanium source.
[0170] Wear resistance test: First clean the surface of the sample with alcohol, then fix the sample on
[0171] In the friction disk of the HT-500 high temperature friction and wear testing machine, Si3N4 ceramic balls with a diameter of 4.763mm (75-80HR) are selected as the grinding material, the grinding radius is 2mm, the test load is 330g, the rotation speed is 560r / min, the wear time is 30min, and the test temperature is 25℃. Before and after the experiment, an electronic balance with an accuracy of 0.1mg is used to weigh the mass loss of the sample before and after wear.
[0172] The performance test results of the target material prepared in the examples of the present application are shown in Table 1.
[0173] Table 1
[0174] - Density(%) Wear amount (mg) Example 1 99.99 0.7 Example 2 99.93 0.9 Example 3 99.91 1.2 Example 4 99.87 1.5 Example 5 99.85 1.8 Example 6 99.81 2.1 Example 7 99.78 2.6 Example 8 99.73 3.2 Example 9 99.62 3.5 Example 10 99.43 5.4
[0175] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A lanthanum-titanium alloy target, characterized in that: The preparation includes the following raw materials: Titanium source, lanthanum source and molybdenum source.
2. The lanthanum-titanium alloy target according to claim 1, characterized in that: The preparation comprises the following raw materials in parts by weight: 100 parts of titanium source, 0.2 to 0.8 parts of lanthanum source and 5 to 10 parts of molybdenum source; And / or, the titanium source is modified sponge titanium; And / or, the method for preparing the modified titanium sponge comprises the following steps: After oxidizing the titanium sponge, an oxidized titanium sponge is obtained; The titanium oxide sponge and the amino silane coupling agent are mixed and then refluxed for reaction.
3. The lanthanum-titanium alloy target according to claim 2, characterized in that: The amino silane coupling agent includes bis-[3-(triethoxysilyl)-propyl]-amine; And / or, the mass ratio of the titanium oxide sponge to the amino silane coupling agent is 100:1-2.
4. The lanthanum-titanium alloy target according to claim 1, characterized in that: The lanthanum source is a carboxylated lanthanum source; And / or, the method for preparing the carboxylated lanthanum source comprises the following steps: The silane, the template agent and the ammonia water are mixed and reacted, and after the reaction is completed, the solid and the liquid are separated, and the solid phase is collected to obtain a first mixture; The first mixture is hydrolyzed, and then the lanthanum salt is added to react.
5. The lanthanum-titanium alloy target according to claim 4, characterized in that: The silane includes isobutyltriethoxysilane or cyanotrimethylsilane; and / or, the template comprises alkylammonium bromide; and / or, the alkylammonium bromide comprises hexadecyltrimethylammonium bromide; and / or, the lanthanum salt comprises at least one of lanthanum chloride or lanthanum nitrate; And / or, the mass ratio of the silane to the template is 1:0.2-0.4; And / or, the mass ratio of the silane to the lanthanum salt is 1:10-20.
6. The lanthanum-titanium alloy target according to claim 1, characterized in that: The molybdenum source is mercapto-modified molybdenum oxide; And / or, the preparation method of the mercapto-modified molybdenum oxide comprises the following steps: Mixing thioglycolic acid, molybdenum oxide and water for post-treatment; And / or, the mass ratio of the molybdenum oxide to thioglycolic acid is 1:0.02-0.
2.
7. A method for preparing a lanthanum-titanium alloy target according to any one of claims 1 to 6, characterized in that: The following steps are involved: The raw materials are mixed, hydrogenated, crushed, cold pressed and hot isostatically pressed.
8. The preparation method according to claim 7, characterized in that: The hydrogenation temperature is 500°C to 600°C; And / or, the hydrogen pressure of the hydrogenation is 0.1MPa to 2MPa; And / or, the hydrogenation time is 2h to 3h; And / or, the cold pressing pressure is 150MPa to 250MPa; And / or, the cold pressing forming time is 5 minutes to 15 minutes.
9. The preparation method according to claim 7, characterized in that: The hot isostatic pressing sintering pressure is 100MPa to 200MPa; And / or, the hot isostatic pressing sintering temperature is 1000° C. to 1400° C.; And / or, the hot isostatic pressing sintering time is 3h to 20h.
10. Use of the lanthanum-titanium alloy target material according to any one of claims 1 to 6 in preparing a sputtering film.